ANALISIS TENGGELAMNYA KM. TEMAN NIAGA DI PERAIRAN SELAT MAKASSAR - Regita Cahyani (2023)
In using ships, safety criteria must be considered and unstable seas that can cause various types of problems such as accidents, sinking, ship damage and others. General cargo ships are ships that carry a variety of cargo in the form of goods. The goods transported are usually packaged goods. General Cargo ships are equipped with freight cranes to facilitate loading and unloading of cargo. KM. Teman Niaga is a cargo ship that transports cement and requires good stability to ensure the safety of the crew. The purpose of this study is to determine the stability of the ship in different wave conditions that can endanger the safety of the crew. BMKG's Ocean Forecast System (OFS) showed strong winds of 15-25 knots from the southeast, moderate wave height of 2.0-3.0 meters. The main causes of ship accidents are bad weather, water ingress, which causes ships to overload and sink. Based on the results of the inclining test, the 5˚ inclination has a maximum GZ value of 39.1 m at an angle of 0.854˚, and the maximum GZ value at 10˚ inclination is 39.1 m at an angle of 0.855˚ and at 15˚ inclination, the maximum GZ value results in a GZ value of 0.834 m at an angle of 45˚. This shows that on a 15˚ slope, the ship takes 0.834 moments to return to its original position.